Present Situation and Prospect of Medical Knowledge Based Systems in German-speaking Countries - Spreckelsen, C.; Spitzer, K.; Honekamp, W. (Methods of Information in Medicine, 2012)
Background: After a decrease of interest in classical medical expert systems, the publication activity concerning the medical application of Artificial Intelligence and the interest in medical decision support have markedly increased. Nonetheless, no systematic exploratory study has yet been carried out, which directly considers the actual fields of applications, exemplary approaches, obstacles, challenges, and future prospect as seen by pioneering users and developers in a given region.Objectives: This paper reports the results of an online survey designed to fill this gap with the “Knowledge Based Systems” working group of the German Society for Medical Informatics, Biometry and Epidemiology (GMDS) in 2010.Methods: The survey was based on an online questionnaire (5 single and multiple choice questions, 8 Likert-scaled items, 7 free text questions) consented to by the working group. The answers were analyzed by descriptive statistics and a qualitative analysis (bottom-up coding). All academic institutions of Medical Informatics in the German-speaking countries and contributors reporting KBS-related projects at the relevant scientific conferences and in a journal specialized in the field were invited to participate.Results: The survey reached a response rate of 33.4%. The results show a gap between the reported obstacles of medical KBS (mainly low acceptance and rare use in clinical practice) and their future prospect as stated by the participants. Problems previously discussed in the literature like low acceptance, integration, and sustainability of KBS projects were confirmed. The current situation was characterized by naming exemplary existing systems and specifying promising fields of application.Conclusions: The field of KBS in medicine is more diversified and has evolved beyond expectations in the German-speaking countries.
Keywords: Knowledge based systems; medicine; online survey; German-speaking countries; potential; future